PERAN ILMU HUSHULI DAN HUDHURI DALAM MEMBUKTIKAN KEBERADAAN TUHAN - Maulana Maulana (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
Hushuli science approach in proving the existence of God uses two burhan, namely burhan inni and burhan limmi. This Burhan in proving the existence of God departs from the effect to the cause. The arguments he uses include the regularity argument (nazham), the form of wa'imkan, and huduts. While burhan limmi in proving the existence of God departs from cause to effect. Hudhuri science is the presence of the essence of something in a person without the intermediary of the senses. In other words, Hudhuri science is the essence of science itself and Hudhuri Science in proving the existence of God through natural arguments.